Review: Analisis Kandungan Logam Berat Timbal Pada Sediaan Bedak Dalam Negeri dan Internasional Menggunakan Metode Spektrofotometri Serapan Atom - Rismiyanti, Aina; Azzahra, Fathia; Chodijah, Siti; Maelaningsih, Firdha Senja (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In this era, the use of cosmetic products in Indonesia has increased significantly. One of the most popular cosmetic products is powder, which contains heavy metals, especially lead, as a colorant. By the provisions of BPOM RI in 2014, the maximum limit of lead heavy metal contamination in cosmetics, including powder, should not exceed 20 mg/kg. As well to the US FDA, which stipulates that the value of lead as an impurity in cosmetic products should not exceed 20 mg/kg. The purpose of this journal review is to assess the levels of lead metal in cosmetic products, especially powder, circulating in various regions in Indonesia and several countries. The literature study method uses secondary data obtained from the Google Scholar database for the last 10 years. 8 articles were found that met the inclusion and exclusion criteria, could be accessed in full text, and had an ISSN number for review. The overall results of the journal review regarding the analysis of heavy metal content, especially lead, were carried out by analyzing solid powder preparations and powders according to atomic absorption spectroscopy (SSA) procedures, which resulted in research-based data.